Return to education by ethnicity in Indonesia - Arsani, Ade Marsinta; Kataoka, Mitsuhiko; Fahmi, Mohammad (JOURNAL OF SOCIOECONOMICS AND DEVELOPMENT, 2023)
Using data from the Indonesia Family Life Survey (IFLS) from 2014–2015, this study seeks to analyze the ethnic differences in the return to education in Indonesia. We discovered that IV models, as opposed to OLS estimation, are more suitable to evaluate returns to education in Indonesia. Additionally, rather than treating the ethnicity variable as an instrumental variable, it is preferable to use it as a grouping variable. After segmenting our samples into six ethnic groups, this study discovered that all ethnic groups, with the exception of the Chinese group, match the IV estimation. The non-Chinese groups with the best returns on schooling are Bataknese and Minangnese. The high return on education in these ethnic groups is attributed to the intense excitement for learning that permeates Bataknese and Minangnese cultures as native cultural assets. Earnings are also influenced favorably by marital status, masculinity, employment in the public sector, and urban-rural location. These findings suggest that ethnic and cultural topics should be covered in the national curriculum as well as local curricula. Since these characteristics have a direct impact on salaries, the government should also pay attention to gender segregation, career opportunities, and urban-rural growth.JEL Classification C26; I26; J15